Tinea Nigra In A Family - Miranda Maria Flora M (Wolters Kluwer Medknow Publications, 2003)
Tinea nigra is a rare superficial fungal infection of the skin affecting mainly the palms. So far, mostly isolated case reports have appeared in the Indian literature. Five cases in a single family are being reported here. The response to treatment is also highlighted.